2010
DOI: 10.1242/jeb.030213
|View full text |Cite
|
Sign up to set email alerts
|

Chewing rates among domestic dog breeds

Abstract: SUMMARYThe mammalian masticatory rhythm is produced by a brainstem timing network. The rhythm is relatively fixed within individual animals but scales allometrically with body mass (M b ) across species. It has been hypothesized that sensory feedback and feedforward adjust the rhythm to match the jaw's natural resonance frequency, with allometric scaling being an observable consequence. However, studies performed with adult animals show that the rhythm is not affected by jaw mass manipulations, indicating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…They showed that, within dogs, CCD scales with body mass 0.07 and jaw length 0.20 , but that there is no correlation between the CCD and either of the morphological variables. Because a non-canid sample matching the sizes of the individual dog breeds yields scaling exponents similar to those obtained from previous interspecific studies, Gerstner and colleagues (Gerstner et al, 2010) propose that the limited size range sampled among the dogs is not a confounding factor in the analysis. More importantly, they argue that the lack of correlation between body size and CCD has a developmental basis.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…They showed that, within dogs, CCD scales with body mass 0.07 and jaw length 0.20 , but that there is no correlation between the CCD and either of the morphological variables. Because a non-canid sample matching the sizes of the individual dog breeds yields scaling exponents similar to those obtained from previous interspecific studies, Gerstner and colleagues (Gerstner et al, 2010) propose that the limited size range sampled among the dogs is not a confounding factor in the analysis. More importantly, they argue that the lack of correlation between body size and CCD has a developmental basis.…”
Section: Introductionmentioning
confidence: 66%
“…Small animals chew at a higher frequency and thus have a shorter chewing cycle duration (CCD) than larger animals (Druzinsky, 1993;Fortelius, 1985;Gerstner et al, 2010;Gerstner and Gerstein, 2008;Ross et al, 2010;Ross et al, 2009a;Ross et al, 2009b;Shipley et al, 1994). Several explanations have been proposed for the observed scaling of CCD with body mass and jaw length.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations